2015
DOI: 10.1016/j.tranon.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Polo-Like Kinases: A Promising Therapeutic Approach for Cancer Treatment

Abstract: Polo-like kinases (Plks) are a family of serine-threonine kinases that regulate multiple intracellular processes including DNA replication, mitosis, and stress response. Plk1, the most well understood family member, regulates numerous stages of mitosis and is overexpressed in many cancers. Plk inhibitors are currently under clinical investigation, including phase III trials of volasertib, a Plk inhibitor, in acute myeloid leukemia and rigosertib, a dual inhibitor of Plk1/phosphoinositide 3-kinase signaling pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
122
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(123 citation statements)
references
References 82 publications
(165 reference statements)
0
122
0
1
Order By: Relevance
“…In human somatic cells, inhibited Plk1 leads to multiple mitotic defects, including the formation of abnormal spindles, misaligned chromosomes and i mproper chromosom e condensation [10]. Additionally, up-or downregulation of Plk1 can induce a variety of human tumor cells or mouse embryonic cell mitotic defects, causing aneuploidy or cancer [11][12][13]. This study shows that Plk1 might play a critical role in the process of bipolar spindle assembly and chromosome arrangement during mitosis in somatic cells.…”
Section: Introductionmentioning
confidence: 73%
“…In human somatic cells, inhibited Plk1 leads to multiple mitotic defects, including the formation of abnormal spindles, misaligned chromosomes and i mproper chromosom e condensation [10]. Additionally, up-or downregulation of Plk1 can induce a variety of human tumor cells or mouse embryonic cell mitotic defects, causing aneuploidy or cancer [11][12][13]. This study shows that Plk1 might play a critical role in the process of bipolar spindle assembly and chromosome arrangement during mitosis in somatic cells.…”
Section: Introductionmentioning
confidence: 73%
“…Role of Plk1 in regulation of nonmitotic events. Plk1 is now recognized as a key regulator in cellular processes with diverse functions (11,41). For example, we previously reported that Plk1 phosphorylation of Topors and GTSE1, two negative regulators of the p53 tumor suppressor, leads to p53 inactivation (42,43) and premature termination of cell cycle arrest due to DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Building off of a sequence similarity to this kinase, as well as an S. Cerivisiae protein involved in the same part of the cell cycle, Cdc5, Golsteyn and colleagues were able to characterize a similar kinase in humans, polo-like kinase 1 (PLK1) (5). Since then, four other members have been added to this family of kinases [reviewed in (6)]. As shown in Figure 1, human Plks 1-4 contain an N terminal kinase domain and vary in the presence of one or more C terminal polo box domains.…”
Section: Introductionmentioning
confidence: 99%